Efficacy Of Apples As A Supplement In Boosting The Lung Capacity Of Aerobic Athletes - Nurliani, Nurliani; Asyhari, Hasbi (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective . Apples nutrients should be able to be used for athletes and athletes who are required to always have excellent physical condition and in short recovery periods, the main physical component for athletes is their cardiovascular and muscular endurance, by knowing how the benefits of apples are nutritious as supplemental supplements, and is also claimed to improve lung function, therefore researchers are interested to observe how the effectiveness of apples as an additional supplement in improving lung capability in athletes aerobic exercise that would require good lung breathing resistance Material and Methods. In this study there is one independent variable and one dependent variable. This research is a descriptive research using Quasi Eksperimen research design. This design begins with an initial test (Pretest) then treated (Treatment) and ends with a final test (Posttest). The population used is all rowing athletes in the city of Makassar. The samples taken were 16 people. The data collection technique uses the Spirometer test.From the calculation result known that the value of Sig. Results. The results of this study (2-tailed) of 0.000 <0.05 it can be concluded that there is effectiveness of apples as a supplement so as to increase lung capacity for aerobic exercise.To find out how much effectiveness of apples as a supplement in increasing lung capacity it can be seen that the correlation is 0.883> 0.05 correlation value is greater than the sig value. this indicates that there is effectiveness of apples as a supplement in increasing lung capacity for aerobic exercise of 88.3%. Conclusion. The lung capacity test of aerobic athletes, specifically rowing athletes from Makassar City, was conducted using a Spirometer. The results indicated that apples were effective as a supplement in enhancing lung capacity for aerobic sports by 88.3%.